Occurrence, impacts, and future challenges of disaster risk in Panama - Quesada Román, Adolfo (2024)
Panama is located in the southernmost portion of Central America, and due to its isthmic location, it is primarily affected by hydrometeorological disasters. Given the limited local-level disaster information available in the country, there is a need to create a review of the natural hazards that most affect its municipalities. Therefore, the DesInventar disaster database with information from 1935 to 2020 was used to identify the most common disasters during this period and where they had the greatest impact. The results indicate that the districts most affected by disasters in Panama are located in the provinces of Panama, Panama Oeste, and Colón. Notable districts include San Miguelito, Colon, La Chorrera, and Arraiján. Furthermore, the most common disasters in Panama, namely floods, landslides, and strong winds, were studied in detail. These results are of vital importance for decision-makers in disaster risk management, land-use planning, and environmental management to generate effective actions and policies to mitigate the effects of disasters in Panama. The study serves as an effective method for developing or tropical countries with similar characteristics.